The relationship between peer relations, self‐rated health and smoking behaviour in secondary vocational schools - Hanna Aho; Anna‐Maija Koivisto; Eija Paavilainen; Katja Joronen (Wiley, 2019)
Abstract Aims To examine the association between peer relations, self‐rated health and smoking behaviour in vocational school setting. Background Smoking in adolescence causes health and socioeconomic inequality in adulthood. There is evidence that smokers are physically less active, have lower academic aspirations and perceive poorer health than non‐smokers. Method The study was conducted in spring 2013 and involved 34,776 vocational students who took part in the School Health Promotion Study in Finland. The associations between adolescent smoking habits and peer relations and smokers' self‐rated health were studied adjusting for the respondents' age, parental education and family type. Results A substantial proportion of the respondents, 37% of the girls and 36% of the boys, reported smoking daily, 15% of the girls and 14% boys smoked occasionally with a further 15% of the girls and 13% of the boys stating that they were ex‐smokers. Of the girls, 33% and 38% of the boys were non‐smokers. Adjusted multinomial regression revealed that having a close friend or friends predicted smoking among girls and boys. Additionally, the adjusted model indicated that being a bully and/or a bully + bully‐victim was associated with smoking behaviour in boys only. Boys and girls who rated their health as moderate or poor were more often daily smokers; in girls, this was also the case in occasional smokers. Conclusion Smoking prevention aimed at vocational schools should take into consideration the norms and expectations related to peer relations which strongly influence adolescents' smoking habits.